Systems pharmacology‐based drug discovery and active mechanism of phlorotannins for type 2 diabetes mellitus by integrating network pharmacology and experimental evaluation. Issue 12 (17th November 2022) - Chen, Jialiang; Li, Ping; Ye, Shuhong; Li, Wei; Li, Ming; Ding, Yan
Abstract: Phlorotannins, polyphenolic compounds that exist only in brown algae, have an effect on T2DM. However, the structure of phlorotannins is complex and diverse, and the complex role of therapeutic targets and active compounds has not been revealed. In this study, the potential targets and pharmacological effects of phlorotannins in the treatment of T2DM were identified based on network pharmacology and enzyme activity inhibition experiment. In total, 15 phlorotannins and 53 associated targets were yielded. Among them, SRC, ESR1, AKT1, HSP90AB1, and AR were defined as core targets. 527 GO biological processes items and 101 KEGG pathways were obtained, including EGFR tyrosine kinase inhibitor resistance, thyroid hormone signaling pathway, AGE‐RAGE signaling pathway in diabetic complications, and VEGF signaling pathway. Phlorotannins could enable resistance against T2DM by inflammatory, survival, gene transcription, proliferation, apoptosis, and atherosclerosis. Finally, α‐glucosidase inhibition assay and molecular docking proved the effect of selected phlorotannins on T2DM. Practical applications: Phlorotannins are a kind of polyphenol compounds that only exists in brown algae. Its structure is polymerized by aromatic precursors phloroglucinol (1, 3, 5‐trihydroxybenzene). They have aroused great interest due to their excellent and valuable biological activities. However, the structure of phlorotannins is complex and diverse, and the complex role of therapeutic targets and active compounds has not been revealed. In this study, the potential targets and pharmacological effects of phlorotannins in the treatment of T2DM were determined basis on network pharmacology and enzyme activity inhibition experiment. In conclusion, the results showed the value of phlorotannins treating on T2DM. Moreover, this study has great significance for improving the medicinal value of phlorotannins and screening natural products for the treatment of T2DM. Abstract : Based on the basic theory, the combination of network pharmacology and experimental evaluation, this study demonstrated the superiority of phlorotannins in the effective substance of T2DM through multi‐target and multi‐channel comprehensive regulation. Exploring the potential functional factors and mechanisms of action in seaweeds can provide a new way to develop new biological agents for treating on T2DM.